MoO3 nanoparticle coatings on high-voltage 5 V LiNi0.5 Mn1.5 O4 cathode materials for improving lithium-ion battery performance - Wu, Zong-Han; Shih, Jeng-Ywan; Li Ying-, Jeng James; Tsai, Yi-De; Hung, Tai-Feng; Karuppiah, Chelladurai; Jose, Rajan; Yang, Chun-Chen (MDPI, 2022)
To reduce surface contamination and increase battery life, MoO3 nanoparticles were coated with a high-voltage (5 V) LiNi0.5 Mn1.5 O4 cathode material by in-situ method during the high-temperature annealing process. To avoid charging by more than 5 V, we also developed a system based on anode-limited full-cell with a negative/positive electrode (N/P) ratio of 0.9. The pristine LiNi0.5 Mn1.5 O4 was initially prepared by high-energy ball-mill with a solid-state reaction, followed by a precipitation reaction with a molybdenum precursor for the MoO3 coating. The typical structural and electrochemical behaviors of the materials were clearly investigated and reported. The results revealed that a sample of 2 wt.% MoO3-coated LiNi0.5 Mn1.5 O4 electrode exhibited an optimal electrochemical activity, indicating that the MoO3 nanoparticle coating layers considerably enhanced the high-rate charge–discharge profiles and cycle life performance of LiNi0.5 Mn1.5 O4 with a negligible capacity decay. The 2 wt.% MoO3-coated LiNi0.5 Mn1.5 O4 electrode could achieve high specific discharge capacities of 131 and 124 mAh g−1 at the rates of 1 and 10 C, respectively. In particular, the 2 wt.% MoO3-coated LiNi0.5 Mn1.5 O4 electrode retained its specific capacity (87 mAh g−1) of 80.1% after 500 cycles at a rate of 10 C. The Li4 Ti5 O12 /LiNi0.5 Mn1.5 O4 full cell based on the electrochemical-cell (EL-cell) configuration was successfully assembled and tested, exhibiting excellent cycling retention of 93.4% at a 1 C rate for 100 cycles. The results suggest that the MoO3 nano-coating layer could effectively reduce side reactions at the interface of the LiNi0.5 Mn1.5 O4 cathode and the electrolyte, thus improving the electrochemical performance of the battery system.